Spectral, electrical, mechanical and dielectric characterization of 2-aminobenzothiazolium 4-fluorobenzoate (Scaffold in drugs) single crystal - Geetha, J Anantha Meena; Jebas, S Robinson (Bangladesh Journal of Scientific and Industrial Research, 2025)
Transparent colourless block single crystal of 2-aminobenzothiazolium 4-fluorobenzoate (2-ABT4FB) was grown from aqueous solution via slow evaporation method. The unit cell parameters of the title compound was determined from single crystal x-ray diffraction studies and found to be a=12.15(9) A, b=12.65(9) A, c=28.3(2) A, α=85.03(18)˚, β=83.00(17)˚, γ=71.30(9)˚. The crystal exhibits wide transparency window of 99%. The band gap energy of the crystal was calculated as 4.11eV from the Tauc’s plot. The sharp emission peak observed at the wavelength of 470 nm in the photoluminescence spectra is due to the blue emission. Mechanical stability of the grown single crystal was investigated by using Vickers microhardness test and reveals that 2-ABT4FB single crystal is the soft material with the Meyer’s index (n) of 2. Single crystal exhibits high dielectric constant at lower frequencies and the dielectric loss decreases as the frequency increases is due to the various polarization effects. Bangladesh J. Sci. Ind. Res. 60(3), 159-168, 2025